Principles and practice of constraint programming : 14th International Conference, CP 2008, Sydney, Australia, September 14-18, 2008 : proceedings - International Conference on Principles and Practice of Constraint Programming; Stuckey, Peter J. (Lecture notes in computer science, 2008)
This volume contains the proceedings of the 14th International Conference on Principles and Practice of Constraint Programming (CP 2008) held in Sydney, Australia, September 14-18, 2008. The conference was held in conjunction with the International Conference on Automated Planning and Scheduling (ICAPS 2008) and the International Conference on Knowledge Representation and R- soning (KR 2008). Information about the conference can be found at the w- sitehttp://www. unimelb. edu. au/cp2008/. Held annually, the CP conference series is the premier international conference on constraint programming. The conference focuses on all aspects of computing with constraints. The CP conf- ence series is organized by the Association for Constraint Programming (ACP). Information about the conferences in the series can be found on the Web at http://www. cs. ualberta. ca/~ai/cp/. Information about ACP can be found athttp://www. a4cp. org/. CP 2008 included two calls for contributions: a call for research papers, - scribing novel contributions in the ?eld, and a call for application papers, - scribing applications of constraint technology. For the ?rst time authors could directly submit short papers for consideration by the committee. The research track received 84 long submissions and 21 short submissions and the application track received 15 long submissions. Each paper received at least three reviews, which the authors had the opportunity to see and to react to, before the papers and their reviews were discussed extensively by the members of the Program Committee.